Acceptability of Drugs in the Treatment of Unresectable/Metastatic BRAF V600-Mutant Melanoma: A Systematic Review and Network Meta-Analysis - Hong, Ling; Huang, Ping; Zheng, Xiaochun; Ye, Xiaolan; Zhao, Hongying; Wang, Jianwei; Shao, Yanfei (Frontiers in Oncology, 2022)
Background: Although many novel regimens have entered the treatment paradigm for unresectable/metastatic BRAF V-600 mutation melanoma, there is still a lack of comparison of head-to-head in terms of security. We conducted a network meta-analysis to compare the risk of adverse events (AEs) across different treatments and to provide an acceptability ranking for patients. Methods: A systematic literature review was conducted in Embase, PubMed, WHO International Clinical Trials Registry Platform, and Clinical Trials.gov with a time frame from database inception to 24 December 2021. We retrieved evidence on the cumulative incidence of any grades AEs and severe AEs based on the pooled risk ratios (RRs) and 95% credible intervals (95% CrI). Results: Twelve publications and thirteen treatments enrolling 5803 patients were included. For any grades AEs, the acceptability of combined dabrafenib and trametinib is superior to the combination of vemurafenib and cobimetinib (RR0.94, Crl 0.89, 0.98). Furthermore, nivolumab in combination with ipilimumab increases any grades AEs than single-agent ipilimumab (RR 0.90, Crl 0.83, 0.96) or nivolumab (RR 0.90, Crl 0.84, 0.97). For severe AEs, dabrafenib has the best acceptability than single-agent vemurafenib (RR0.66, Crl 0.50, 0.87) or encorafenib (RR0.64, Crl 0.43, 0.94). In addition, ipilimumab (SUCRA: 0.87) ranks first in the acceptability for any grades AEs, and nivolumab (SUCRA: 0.95) ranks first in the acceptability for severe AEs. The ranking of the combination of vemurafenib and cobimetinib (SUCRA: 0.66) is superior than encorafenib in combination with binimetinib (SUCRA: 0.39) and combination of vemurafenib and cobimetinib (SUCRA: 0.18). Conclusions: We identified the lowest AE risk treatment options for BRAF V-600 mutation melanoma patients. In general, immunotherapy (ipilimumab or nivolumab) has better acceptability than most targeted therapies, and triplet therapies are related with the worst acceptability. Moreover, single-agent dabrafenib can be used as the first choice in mono-therapy, and the combination of dabrafenib and trametinib is the preferred combination therapy. Overall, the combination of immunotherapy drugs increases any grades and severe AEs than a single agent, whereas the condition of targeted therapy drugs cannot be simply generalized. Therefore, this information can facilitate evidence-based decision-making and support optimizing treatment and outcomes in clinical practice.